Effects of polycarboxylate superplasticizer on rheological properties and early hydration of natural hydraulic lime. (September 2021) - Zhu, Jianfeng; Hui, Jing; Luo, Hongjie; Zhang, Biao; Wei, Xiaohong; Wang, Fen; Li, Yunfeng
Abstract: As one of the main materials for grouting repair, the workability of natural hydraulic lime (NHL) has been concerned widely. In this paper, effects of polycarboxylate superplasticizer (PCE) on rheological properties and early hydration of natural hydraulic lime (NHL2) and their correlations were systematically investigated. Results show that the fluidity of NHL2 paste improves significantly and tends to a stable state at a certain dosage in the presence of PCE. It is found that PCE makes the flocculated structures in paste disassemble and produces more small particles. The results can lead to a decrease in yield stress and plastic viscosity, further improving rheological properties. The retardation effect of PCE on NHL2 hydration can depress the crystallization and early formation of calcium hydroxide Ca(OH)2 and calcium silicate hydrate (C–S–H). The effect can reduce water consumption during mixing, which has a positive influence on rheological properties.